Rent : Between the resource curse, Economic corruption and the impact of the current crisis - Analytical Study of the inconvenient of oil in Algeria- - Halimi, Hakima (Milev Journal of Research and Studies, 2017)
This study aims to reveal the disadvantages of oil in Algeria through three basic axes, First We discussed about the natural resource curse that has remained inherent renter states, by searching the symptoms and mechanisms of Dutch disease In the Algerian economy, second We reviewed the resulting oil revenues, Especially in the economic side, Through the analysis of the relationship between them, Finally, we pointed out the repercussions of the oil crisis on the national economy, the study concluded that Oil revenues contributed to the financing of development schemes for decades, but its negative effects imposed the need to move the national economy has a renter nature into a productive economy through a comprehensive program of economic diversification.